EVALUASI INLET DRAINASE JALAN POROS UTAMA KECAMATAN KUALA KABUPATEN NAGAN RAYA - Uswatun Hasanah; Eldina Fatimah; Azmeri Azmeri (Prodi Magister Teknik Sipil Unsyiah, 2018)
Nagan Raya District Government undertook the construction of roads, including the Poros Utama Road of Kuala Subdistrict. At the time of rain, in certain locations are still formed puddles above the surface of the asphalt. Therefore, it is necessary to evaluate the efficiency and duration of draining flow through the inlet on the road. The data required are the type, distance and dimensions of the existing inlet and the location map, the maximum daily annual rainfall data, cross and longitudinal sectional drawing. Calculations start by calculating the design flow of rainfall data processing. Furthermore, the calculation of the gutter flow as well as the efficiency and the inlet draining time. Based on calculations, the efficiency of the existing inlet in the form of a curb opening inlet is in the range between 4,93% to 6,51% with 0,64-3,92 minutes of draining time. This value indicates that the inlet on the road produces very low efficiency. Inlet is expected to drain all the water or 100% efficiency. The inundation disturbs the movement of the vehicle and affects the pavement resistance. Therefore, the flow of water above the road surface is expected not to create a puddle.